Development of Characterized Digital Comics for Junior High School Students in Social Studies Learning - Usmaedi; Maftuh, Bunyamin; Hamdan; Nurbayani K, Siti; Siswanto, Puji (JTP - Jurnal Teknologi Pendidikan, 2023)
This study is aimed at developing the material for social science study at Junior High School by using characterized digital comics. The study uses a research and development model popularized by Borg and Gall. The types of data used in this research are qualitative and quantitative data. Qualitative data was obtained based on criticism and suggestions for improvement from validators. Quantitative data was obtained based on the results of filling out a questionnaire in the form of objective product assessment scores. The instruments used for data collection were open and closed questionnaires. Based on the results of data analysis from media experts, a feasibility value was obtained from media experts 149 a maximum value of 152 so that a percentage of 98% was obtained, from material experts a feasibility value was obtained of 112 from a maximum value of 114 so that a percentage of 98% was obtained, and the results of scale group trials limited (10 students) obtained a score of 890 out of a total of 1000 so that a percentage of 89% was obtained. This shows that the digital comic with characters being developed is classified as "very valid" and can be implemented. In brief, the results of developing digital comics with characters are appropriate and can be recommended to be used in social science studies at junior high schools.